(untitled) (Mongolian Journal of Agricultural Sciences, 2015)
Drought, cold and salinity are the primary factors limiting wheat production. It has been shown that a wheat stress-responsive WRKY transcription factor encoded by the wheat WRKY10 gene plays an important role in drought, cold and salinty stress tolerance. The aim of the current study was to WRKY10 gene expression in drought, cold and salinity up-regulated in six varieties of Mongolian local wheat (Triticum aestivum L.), to select the stress tolerant best variety for breeding program. Plants expressing TaWRKY10 was up-regulated 48 hours stress by treatment with polyethylene glycol (PEG6000), 200 mM NaCl and 40C cold. Results of RT-PCR indicate that the all varieties show the gene expression level. Furthermore, reverse transcription polymerase chain reactions revealed that the expressions of WRKY 10 genes involved in abiotic stress signaling of six wheat varieties. These results indicated highest expression level of the WRKY10 in Darkhan-131 and lowest expression in Darkhan-34. And our study provided a promising approach to improve the tolerances of wheat cultivars to drought and salinity varieties of selection materials. Mongolian Journal of Agricultural Sciences Vol.13(2) 2014: 136-140